2008
DOI: 10.2353/ajpath.2008.070633
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligand Promotes Mac-1 Expression, Leukocyte Recruitment, and Neointima Formation after Vascular Injury

Abstract: High levels of circulating soluble CD40 ligand (sCD40L) are frequently found in patients with hypercholesterolemia, diabetes, ischemic stroke, or acute coronary syndromes, predicting an increased rate of atherosclerotic plaque rupture and restenosis after coronary/carotid interventions. Clinical restenosis is characterized in part by exaggerated neointima formation, but the underlying mechanism remains incompletely understood. This study investigated the role of elevated sCD40L in neointima formation in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 60 publications
4
80
2
6
Order By: Relevance
“…Although Li and colleagues (37) reported that stimulation of neutrophils with soluble CD40L led to their increased expression of Mac-1, we have not observed any difference in the level of Mac-1 (CD11b) expression on cells stimulated with sCD40L. This could be because the cells (macrophages) already expressed very high levels of CD11b (data not shown), and thus it was difficult to further increase their expression.…”
Section: Discussioncontrasting
confidence: 43%
“…Although Li and colleagues (37) reported that stimulation of neutrophils with soluble CD40L led to their increased expression of Mac-1, we have not observed any difference in the level of Mac-1 (CD11b) expression on cells stimulated with sCD40L. This could be because the cells (macrophages) already expressed very high levels of CD11b (data not shown), and thus it was difficult to further increase their expression.…”
Section: Discussioncontrasting
confidence: 43%
“…34,35,[38][39][40] In our study, high levels of the immune activation markers TLR2, TLR4 and PD-L1 were found on all three monocyte subsets. sCD14 and sCD163 are monocyte/macrophage activation markers.…”
Section: Cd16mentioning
confidence: 99%
“…Enhancement of the oxidative stress has been reported in patients with HUS [36,37] and vascular diseases which have also been associated with elevated levels of plasma sCD40L as has been discussed above [52][53][54]. In this regard, other authors have previously reported that recombinant human CD40L promotes oxidative burst in human neutrophils via a PI3-kinase-dependent signaling pathway [30,55,56] and Vanichakarn et al described a positive feedback loop between platelets and neutrophils, similar to that reported in our study between platelets and monocytes [30].…”
Section: Discussionmentioning
confidence: 87%